Conductive antibacterial polyurethane foam and preparation method and application thereof
By modifying graphene and silver nanoparticles on polyurethane foam, the problem of insufficient conductivity and antibacteriality of polyurethane foam in the field of flexible wearable electronic devices is solved, and the material is multifunctionalized, and it is suitable for health monitoring and medical treatment applications.
Patent Information
- Application Number
- CN202411255012.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The application of polyurethane foam in the field of flexible wearable electronic devices is limited by its electrical conductivity and antibacterial properties, and existing antibacterial doses are large and may damage material properties.
By co-soluble trisodium citrate and carboxylated chitosan with silver salt, silver nanosolution was prepared, and the graphene suspension and polyurethane foam were sonicated to fix the graphene inside the foam, combining the antibacterial effect of the silver nanoparticles, and improving conductivity and antibacterial properties were achieved.
It has achieved the improvement of the conductivity and antibacterial properties of polyurethane foam, has good biosafety and environmental friendliness, and is suitable for flexible wearable electronic devices.
Smart Images

Figure CN118755145B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane foam materials, and specifically relates to a conductive antibacterial polyurethane foam and a preparation method and application thereof. Background Art
[0002] In recent years, the demand for stretchable and flexible wearable electronic devices for health monitoring and medical treatment connected to the human body has been growing. Polyurethane foam, an advanced functional material with excellent mechanical flexibility, light weight, good biocompatibility and processability, is a good choice for the production of such wearable products. However, polyurethane foam is an insulator and cannot conduct electricity, and its porous structure is a breeding ground for bacteria, which greatly hinders its application in the field of flexible wearable electronic devices. Existing antibacterial polyurethane foam is usually produced by blending antibacterial agents with polyurethane foam raw materials. This method not only requires a large amount of antibacterial agents, but also destroys the characteristics of the polyurethane foam itself to a certain extent, and the resulting polyurethane foam is not conductive. Therefore, how to make polyurethane foam multifunctional without destroying the original mechanical flexibility and elasticity of polyurethane foam, and how to make it conductive while having antibacterial properties, is one of the challenges faced in enabling its application in the field of wearable electronic devices. Silver nanoparticles have a strong bactericidal effect on both Escherichia coli and Staphylococcus aureus, and are an excellent broad-spectrum antibacterial material. Compared with other antibacterial metals, silver nanoparticles are less toxic to mammalian cells. Therefore, many researchers choose to use silver nanoparticles to improve the antibacterial properties of polymers. In addition, silver nanoparticles also have excellent conductivity, but silver nanoparticles have poor dispersibility. Agglomerated silver nanoparticles not only have a greatly reduced antibacterial effect, but also increase their biological toxicity. The effective solution to this problem can provide valuable functional structures and materials for flexible wearable electronic devices. Summary of the invention
[0003] In view of the above-mentioned prior art, the present invention discloses a conductive antibacterial polyurethane foam and a preparation method and application thereof, so as to solve the technical problem of poor conductivity and antibacterial properties of polyurethane foam in the prior art.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing conductive antibacterial polyurethane foam, which comprises the following steps:
[0005] S1: dissolving trisodium citrate and carboxylated chitosan in water, then adding silver salt, stirring the solution for 28-35 minutes in a dark environment, and then stirring at 70-80°C for 60-75 minutes to obtain a silver nano solution;
[0006] S2: adding graphene powder into a solvent and obtaining a graphene suspension after ultrasonic dispersion;
[0007] S3: placing the cleaned polyurethane foam in the graphene suspension and ultrasonicating, and then cleaning and drying the polyurethane foam to obtain a modified polyurethane foam; the ultrasonic time is 15 to 30 minutes, and the ultrasonic frequency is 19 to 23 kHz;
[0008] S4: immersing the modified polyurethane foam in the silver nano solution for 10 to 60 minutes, taking it out and drying it.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Furthermore, in step S1, the silver salt is silver nitrate or silver acetate; the material-liquid ratio of trisodium citrate, carboxylated chitosan, water and silver salt is 6~15mg:3~9mg:9~12mL:0.75~3mg.
[0011] Furthermore, in step S2, the graphene powder is single-layer graphene powder, multi-layer graphene powder, reduced graphene oxide powder or graphene oxide powder; the solvent is a mixed solvent consisting of anhydrous ethanol and solvent A, and solvent A is N,N-dimethylformamide, dichloromethane, tetrahydrofuran, butanone, cyclohexanone, acetone, ethyl acetate or toluene; and the volume ratio of anhydrous ethanol to solvent A is 2~3:2.
[0012] Further, the concentration of graphene in the graphene suspension in step S2 is 2-30 mg / mL.
[0013] Further, the concentration of graphene in the graphene suspension in step S2 is 15-25 mg / mL.
[0014] Furthermore, in step S2, the ultrasonic time is 30-35 min, and the ultrasonic frequency is 35-45 kHz.
[0015] Furthermore, the equipment for ultrasonic treatment in step S3 is an ultrasonic cell pulverizer.
[0016] Furthermore, the drying temperature in steps S3 and S4 is 55-65°C.
[0017] The invention also discloses the use of polyurethane foam in preparing flexible antibacterial wearable electronic devices.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention adopts safe, non-toxic and environmentally friendly trisodium citrate and carboxylated chitosan to reduce silver ions, wherein trisodium citrate is used as a reducing agent and carboxylated chitosan is used as a stabilizer and an auxiliary reducing agent, and successfully prepares silver nanoparticles with high stability and uniform particle size at a relatively low temperature; the silver nanoparticles with broad-spectrum bactericidal properties not only give the polyurethane foam the ability to resist bacterial and viral biological growth, but also improve the electrical conductivity of the polyurethane foam; and the silver nano solution prepared by the present invention can be used repeatedly.
[0020] 2. The present invention uses high-energy ultrasonic technology to firmly and vertically insert and fix graphene on the surface of the internal pore wall of the polyurethane foam without destroying the structure of the polyurethane foam itself. Graphene has a high specific surface area and excellent conductivity, provides excellent loading sites for silver nanoparticles, and solves the problem of easy agglomeration of silver nanoparticles to a great extent; at the same time, the exposed edges of the vertically inserted graphene can play a nano-blade cutting effect, thereby improving its destructive and killing effect on cells such as bacteria and viruses; in addition, the graphene tightly arranged in scales provides an excellent internal conductive network for the polyurethane foam, so that it obtains good conductivity.
[0021] 3. The preparation process of the present invention is simple, and no toxic reactants are used in the preparation of silver nanoparticles, and the entire reaction process is green, safe and pollution-free.
[0022] 4. The polyurethane foam prepared by the present invention has excellent antibacterial properties, and the sterilization rate against Escherichia coli and Staphylococcus aureus can reach more than 99.99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a diagram of the electrical response signal generated when the polyurethane foam prepared in Example 3 is adhered to the human knee joint during knee bending and straightening. DETAILED DESCRIPTION
[0024] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0025] Example 1
[0026] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0027] S1: At room temperature, 9 mg of trisodium citrate and 5 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 0.75 mg of silver nitrate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 60 min to obtain a silver nanoparticle solution.
[0028] S2: 1000 mg of reduced graphene oxide powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of N,N-dimethylformamide, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 30 min, the ultrasonication frequency was 40 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 20 mg / mL was obtained;
[0029] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20min, the ultrasonic frequency is 23kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 60°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0030] S4: The modified polyurethane foam was immersed in the silver nano-solution for 15 minutes, and then taken out and dried in a 60°C constant temperature drying oven to constant weight.
[0031] Example 2
[0032] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0033] S1: At room temperature, 9 mg of trisodium citrate and 3 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 1.5 mg of silver nitrate was added to the solution. The solution was stirred for 28 min in a dark environment, and then transferred to a 70°C oil bath and stirred for 60 min to obtain a silver nanoparticle solution.
[0034] S2: 1000 mg of reduced graphene oxide powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of N,N-dimethylformamide, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 30 min, the ultrasonication frequency was 40 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 20 mg / mL was obtained;
[0035] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20min, the ultrasonic frequency is 19kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 60°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0036] S4: The modified polyurethane foam was immersed in the silver nano-solution for 15 minutes, and then taken out and dried in a 60°C constant temperature drying oven to constant weight.
[0037] Example 3
[0038] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0039] S1: At room temperature, 9 mg of trisodium citrate and 5 mg of carboxylated chitosan were stirred and dissolved in 12 mL of deionized water, and then 3 mg of silver nitrate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 60 min to obtain a silver nanoparticle solution.
[0040] S2: 900 mg of reduced graphene oxide powder was added to a mixed solvent consisting of 25 mL of anhydrous ethanol and 20 mL of tetrahydrofuran, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 32 min, the ultrasonication frequency was 40 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 20 mg / mL was obtained;
[0041] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 30min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 65°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0042] S4: The modified polyurethane foam is immersed in the silver nano-solution for 20 minutes, taken out and dried in a 65°C constant temperature drying oven to constant weight.
[0043] Example 4
[0044] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0045] S1: At room temperature, 9 mg of trisodium citrate and 6 mg of carboxylated chitosan were stirred and dissolved in 10 mL of deionized water, and then 3 mg of silver acetate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 75 min to obtain a silver nano solution.
[0046] S2: 1.5 g of multilayer graphene powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of butanone, and the mixed solution was uniformly dispersed by ultrasonic treatment. The ultrasonic time was 32 min, the ultrasonic frequency was 35 kHz, and the power was 120 W. After ultrasonic treatment, a graphene suspension with a graphene concentration of 30 mg / mL was obtained.
[0047] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 15min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 55°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0048] S4: The modified polyurethane foam was immersed in the silver nano-solution for 60 minutes, and then taken out and dried in a 55°C constant temperature drying oven to constant weight.
[0049] Example 5
[0050] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0051] S1: At room temperature, 9 mg of trisodium citrate and 6 mg of carboxylated chitosan were stirred and dissolved in 10 mL of deionized water, and then 3 mg of silver acetate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 75 min to obtain a silver nano solution.
[0052] S2: 1 g of multilayer graphene powder was added to a mixed solvent consisting of 20 mL of anhydrous ethanol and 20 mL of acetone, and the mixed solution was uniformly dispersed by ultrasonic treatment. The ultrasonic time was 32 min, the ultrasonic frequency was 35 kHz, and the power was 120 W. After ultrasonic treatment, a graphene suspension with a graphene concentration of 25 mg / mL was obtained.
[0053] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 15min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 55°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0054] S4: The modified polyurethane foam was immersed in the silver nano-solution for 60 minutes, and then taken out and dried in a 55°C constant temperature drying oven to constant weight.
[0055] Example 6
[0056] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0057] S1: At room temperature, 15 mg of trisodium citrate and 9 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 3 mg of silver nitrate was added to the solution. The solution was stirred for 35 min in a dark environment, and then transferred to an oil bath at 80 ° C and stirred for 70 min to obtain a silver nano solution;
[0058] S2: 750 mg of graphene oxide powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of ethyl acetate, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 30 min, the ultrasonic frequency was 40 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 15 mg / mL was obtained;
[0059] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 30min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 65°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0060] S4: The modified polyurethane foam is immersed in the silver nano-solution for 45 minutes, taken out and dried in a 65°C constant temperature drying oven to constant weight.
[0061] Example 7
[0062] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0063] S1: At room temperature, 6 mg of trisodium citrate and 3 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 3 mg of silver nitrate was added to the solution. The solution was stirred for 28 min in a dark environment, and then transferred to a 70°C oil bath and stirred for 60 min to obtain a silver nano solution.
[0064] S2: 400 mg of single-layer graphene powder was added to a mixed solvent consisting of 20 mL of anhydrous ethanol and 20 mL of dichloromethane, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 30 min, the ultrasonication frequency was 35 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 10 mg / mL was obtained;
[0065] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20min, the ultrasonic frequency is 19kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 60°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0066] S4: The modified polyurethane foam was immersed in the silver nano-solution for 15 minutes, and then taken out and dried in a 60°C constant temperature drying oven to constant weight.
[0067] Example 8
[0068] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0069] S1: At room temperature, 9 mg of trisodium citrate and 5 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 3 mg of silver acetate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 60 min to obtain a silver nano solution.
[0070] S2: 125 mg of multilayer graphene powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of cyclohexanone, and the mixed solution was uniformly dispersed by ultrasonic treatment. The ultrasonic time was 35 min, the ultrasonic frequency was 45 kHz, and the power was 120 W. After ultrasonic treatment, a graphene suspension with a graphene concentration of 2.5 mg / mL was obtained.
[0071] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20min, the ultrasonic frequency is 23kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 60°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0072] S4: The modified polyurethane foam was immersed in the silver nano-solution for 15 minutes, and then taken out and dried in a 60°C constant temperature drying oven to constant weight.
[0073] Example 9
[0074] A conductive antibacterial polyurethane foam, the preparation method of which comprises the following steps:
[0075] S1: At room temperature, 9 mg of trisodium citrate and 6 mg of carboxylated chitosan were stirred and dissolved in 10 mL of deionized water, and then 3 mg of silver acetate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 70 min to obtain a silver nano solution.
[0076] S2: 100 mg of multilayer graphene powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of toluene, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 32 min, the ultrasonication frequency was 35 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 2 mg / mL was obtained;
[0077] S3: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 15min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, wash the ultrasonicated polyurethane foam with a 50wt% ethanol aqueous solution, wash it until the ethanol aqueous solution is clear, and then place it in a 55°C constant temperature drying oven to dry to constant weight to obtain a modified polyurethane foam;
[0078] S4: The modified polyurethane foam was immersed in the silver nano-solution for 60 minutes, and then taken out and dried in a 55°C constant temperature drying oven to constant weight.
[0079] Comparative Example 1
[0080] The commercial polyurethane foam was placed in a 50wt% ethanol aqueous solution and stirred for cleaning. After being taken out, it was placed in deionized water and stirred for cleaning. After repeating the above cleaning operation three times, the polyurethane foam was placed in a 60°C constant temperature drying oven and dried until the mass was constant to obtain a cleaned polyurethane foam.
[0081] Comparative Example 2
[0082] A polyurethane foam, the preparation method of which comprises the following steps:
[0083] S1: 1000 mg of reduced graphene oxide powder was added to a mixed solvent consisting of 30 mL of anhydrous ethanol and 20 mL of N,N-dimethylformamide, and the mixed solution was uniformly dispersed by ultrasonication. The ultrasonication time was 30 min, the ultrasonication frequency was 40 kHz, and the power was 120 W. After ultrasonication, a graphene suspension with a graphene concentration of 20 mg / mL was obtained;
[0084] S2: Place commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above cleaning operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a graphene suspension, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20 min, the ultrasonic frequency is 22kHz, the ultrasonic power is 300W, and the ultrasonicated polyurethane foam is washed with a 50wt% ethanol aqueous solution until the ethanol aqueous solution is clear, and then placed in a 60°C constant temperature drying oven to dry to constant weight.
[0085] Comparative Example 3
[0086] A polyurethane foam, the preparation method of which comprises the following steps:
[0087] S1: At room temperature, 9 mg of trisodium citrate and 5 mg of carboxylated chitosan were stirred and dissolved in 9 mL of deionized water, and then 3 mg of silver acetate was added to the solution. The solution was stirred for 30 min in a dark environment, and then transferred to a 75°C oil bath and stirred for 60 min to obtain a silver nano solution.
[0088] S2: Place the commercial polyurethane foam in a 50wt% ethanol aqueous solution, stir and wash it, take it out and place it in deionized water, stir and wash it, repeat the above washing operation three times, place the polyurethane foam in a 60°C constant temperature drying oven, dry it to constant mass, then place the cleaned polyurethane foam in a mixed solvent consisting of 30mL anhydrous ethanol and 20mL N,N-dimethylformamide, and place it in an ultrasonic cell crusher for high-energy ultrasonic treatment, the ultrasonic time is 20min, the ultrasonic frequency is 23kHz, the ultrasonic power is 300W, and the ultrasonicated polyurethane foam is washed with a 50wt% ethanol aqueous solution until the ethanol aqueous solution is clear, and then placed in a 60°C constant temperature drying oven to dry to constant weight;
[0089] S3: The dried polyurethane foam is immersed in the silver nano-solution for 15 minutes, taken out and dried in a 60°C constant temperature drying oven until constant weight is obtained.
[0090] Experimental example
[0091] 1. Antibacterial performance test
[0092] (1) The bactericidal effect of the polyurethane foams in the examples and comparative examples on Escherichia coli was tested by colony counting method. A polyurethane foam with a size of 10 mm × 10 mm × 0.6 mm was placed in 10 mL of a flask containing 1 × 10 6CFU / mL bacterial suspension. Comparative Example 1 was used as the control group, and Examples 1-9 and Comparative Examples 2-3 were used as the experimental groups; after shaking and culturing for 90 min in a constant temperature shaker at 220 rpm and 37°C, the suspension was diluted 100 times, and 30uL of the bacterial suspension in the control group and the experimental group was spread on an agar plate for bacterial counting.
[0093] (2) The bactericidal effect of the polyurethane foam in the examples and comparative examples on Staphylococcus aureus was tested by colony counting method. A polyurethane foam with a size of 10 mm × 10 mm × 0.6 mm was placed in 10 mL of a flask containing 1 × 10 6 CFU / mL bacterial suspension. Comparative Example 1 was used as the control group and Example 3 was used as the experimental group; after shaking and culturing for 90 min in a constant temperature shaker at 220 rpm and 37°C, the suspension was diluted 100 times, and 30uL of the bacterial suspension in the control group and the experimental group was spread on an agar plate for bacterial counting.
[0094] The calculation formula of antimicrobial rate (AR) is as follows:
[0095]
[0096] Where b and c are the average values of colony counts in the control group and the experimental group, respectively. The test results are shown in Table 1.
[0097] Table 1 Antibacterial test results of Examples 1 to 9 and Comparative Examples 1 to 3
[0098]
[0099] Example 3 has a very strong bactericidal effect on Staphylococcus aureus. All Staphylococcus aureus are killed within 90 minutes, and the antibacterial rate can reach 100%.
[0100] 2. Conductivity test
[0101] The resistance value R of the polyurethane foam prepared in Examples 1 to 9 and Comparative Examples 2 to 3 was tested using a multimeter, and the conductivity σ thereof was calculated using the formula as follows:
[0102]
[0103] Wherein L is the length of the sample, A is the cross-sectional area, and the calculation results are shown in Table 2. The sample of Comparative Example 1 is commercial polyurethane foam, which is not conductive.
[0104]
[0105] Table 2 Conductivity test results of Examples 1 to 9 and Comparative Examples 2 to 3
[0106] The polyurethane foam prepared in Example 3 has strong antibacterial properties against Escherichia coli and Staphylococcus aureus, and the sterilization rate reaches 100%. For Comparative Example 3 modified only with silver nanoparticles, although it has a high sterilization effect, its conductivity is very low as shown in the conductivity test results in Table 2, while the conductivity of Examples 1 to 9 with the addition of graphene is significantly improved, especially Example 3, the conductivity of which is 1 to 2 orders of magnitude higher than that of Comparative Examples 2 to 3.
[0107] As another example, the polyurethane foam prepared in Example 3 was pasted on the human knee joint, and the electrical response signal generated during the bending and straightening of the knee was recorded using a CHI 760E electrochemical analyzer. The results are shown in Figure 1 This proves that the polyurethane foam of the present invention will produce different electrical signal responses when different strains occur, and thus can be used to monitor the movement state of the human body.
[0108] In summary, the polyurethane foam modified by graphene-silver nanoparticles in the present invention has both conductive and antibacterial properties and can be applied in the field of flexible wearable electronic devices.
[0109] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing a conductive antibacterial polyurethane foam, characterized in that: The following steps are involved: S1: dissolving trisodium citrate and carboxylated chitosan in water, then adding silver salt, stirring the solution for 28-35 minutes in a dark environment, and then stirring at 70-80°C for 60-75 minutes to obtain a silver nano solution; The material-liquid ratio of trisodium citrate, carboxylated chitosan, water and silver salt is 6~15mg:3~9mg:9~12mL:0.75~3mg; S2: adding graphene powder to a solvent, and obtaining a graphene suspension after ultrasonic dispersion; the graphene powder is a single-layer graphene powder, a multi-layer graphene powder or a reduced graphene oxide powder; the solvent is a mixed solvent consisting of anhydrous ethanol and a solvent A, and the solvent A is N,N-dimethylformamide, dichloromethane, tetrahydrofuran, butanone, cyclohexanone, acetone, ethyl acetate or toluene; the concentration of graphene in the graphene suspension is 2-30 mg / mL; S3: placing the cleaned polyurethane foam in the graphene suspension and ultrasonicating, and then cleaning and drying the polyurethane foam to obtain a modified polyurethane foam; the ultrasonic time is 15 to 30 minutes, and the ultrasonic frequency is 19 to 23 kHz; S4: immersing the modified polyurethane foam in the silver nano solution for 10 to 60 minutes, taking it out and drying it.
2. The preparation method according to claim 1, characterized in that: The silver salt is silver nitrate or silver acetate.
3. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of anhydrous ethanol to solvent A is 2-3:
2.
4. The preparation method according to claim 3, characterized in that: The concentration of graphene in the graphene suspension in step S2 is 15-25 mg / mL.
5. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic time is 30-35 min, and the ultrasonic frequency is 35-45 kHz.
6. The preparation method according to claim 1, characterized in that: The equipment for ultrasonic treatment in step S3 is an ultrasonic cell pulverizer.
7. The preparation method according to claim 1, characterized in that: The drying temperature in steps S3 and S4 is 55-65°C.
8. A conductive antibacterial polyurethane foam, characterized in that: The conductive antibacterial polyurethane foam is prepared by the method for preparing the conductive antibacterial polyurethane foam according to any one of claims 1 to 7.
9. An application of conductive antibacterial polyurethane foam, characterized in that: The polyurethane foam described in claim 8 is used to prepare flexible antibacterial wearable electronic devices.
Citation Information
Patent Citations
Method for preparing nanometer sliver colloid with liquid phase reduction method
CN104815990A